Characterization of structures and gel properties of ultra-high-pressure treated-myofibrillar protein extracted from mud carp (Cirrhinus molitorella) and quality characteristics of heat-induced sausage products. (1st August 2022) - Liu, Qiaoyu; Lin, Zeqian; Chen, Xiaomei; Chen, Junwen; Wu, Junshi; Chen, Haiguang; Zeng, Xiaofang
Abstract: This study aimed to understand the effects of ultra-high pressure (UHP) treatment on the protein structures and gel properties of myofibrillar protein (MP), and the secondary structure and quality of sausage gels developed by Cirrhinus molitorella . MP was treated with 100, 200, and 300 MPa for 3, 9, and 15 min separately. Observations suggested that UHP treatment improved MP aggregation α-helix and β-Sheet converted to random coil in MP structures as pressure increased. Myosin heavy chain (180 kDa) and actin (48 kDa) are the most important protein bands in C. molitorella MP. When the pressure reached to 300 MPa for 9 min during UHP-thermal processing, the gel strength, water holding capacity, and the chewiness and hardness of fish sausage gels reached to the peak value of 1, 296.8 g cm, 83.60%, 3864.02 g/mm and 2169.94 g, respectively. 300 MPa for 9 min was the optimum UHP condition to modify the conformation to improve gel properties of MP, and to improve the quality characteristics of heat-induced sausage gels. Collectively, UHP had the potential in expanding the application of fish protein in food industry by modifying MP structure, as well as in developing novel fish products. Graphical abstract: Image 1 Highlights: UHP treatment improved protein aggregation in C. molitorella MP. Increasing pressure induced regular structure converting to random coil in MP. 300 MPa for 9 min was the optimum UHP condition to improve MP gel properties. Thermal processing improved quality properties of UHP-treated sausage products. UHP and thermal treatments had the potential in developing C. molitorella sausage products.